(untitled) (Philippines, 2016)
Contents: ASEAN regional plan of action on the elimination of violence against children; declaration on the elimination of violence against women and elimination of violence against children in ASEAN (2013); Hanoi declaration on the enhancement of wekfare and development of ASEAN women and children...
Keywords: Quyền trẻ em,Children's rights